HUBUNGAN KEMAMPUAN KERJA DAN MOTIVASI DENGAN KINERJA PEGAWAI DI BADAN PUSAT STATISTIK KABUPATEN BATANG - Oktaviana Tri Setyorini; Endang Larasati; Susi Sulandari (Journal of Public Policy and Management Review, 2015)
Less than optimal performance of employees at Central Agency of Statistics in Batang has prompted the authors to conduct the study, entitled "Relationship Work Ability and Motivation With Employee Performance at Central Agency of Statistics in Batang ". The main problem in this study is less optimal level of work ability and motivation. This study aimed to determine the relationship and determination of each independent variable with the ability to work and motivation of employees in the performance of the Central Agency of Statistics in Batang.This type of research is explanatory research. The data were collected by distributing questionnaires to the respondents and conduct interviews. This study used a sample of 32 respondents to the poll saturated sample technique. Analysis of the data in this study using quantitative methods. Analysis tool used in this research is the analysis of Rank Correlation Coefficient Kendall, Kendall concordance coefficient, and the coefficient of determination by using SPSS version 16.0.The results of this study indicate that there is a positive and significant relationship between the independent variable and motivation with the ability to work performance of employees in BPS, Batang. The magnitude of the relationship of each variable is as follows: the ability to work (0.453) and motivation (0.439). Relations between the two independent variables together to employee performance 0.763 with the influence of 58.21%.